Review. Issue 1 (1st June 2019) - Merwe, Ragnar van der; Roos, Carlos M.
Scientific Ontology: Integrating Naturalized Metaphysics and Voluntarist Epistemology, Anjan Chakravartty (2017) New York: Oxford University Press, 296 pp., ISBN 978 0 19065 145 9, h/bk, £53.00The Discursive-Material Knot: Cyprus in Conflict and Community Media Participation, Nico Carpentier (2017) New York: Peter Lang Publishing, 471 pp., ISBN 978 1 43313 753 2, p/bk, €55.95